Lung bioavailability of generic and innovator salbutamol metered dose inhalers. Issue 3 (March 1996) - Clark, D J; Gordon-Smith, J; McPhate, G; Clark, G; Lipworth, B J
Abstract : BACKGROUND: The aim of this study was to determine whether significant differences exist in lung bioavailability between generic (Salamol, Salbulin) and innovator (Ventolin) formulations of inhaled salbutamol given by metered dose inhalers. METHODS: Ten healthy volunteers of mean age 20.5 years with a forced expiratory volume in one second (FEV1) of 112.1% predicted were studied in a randomised double blind single dosing crossover study. Salbutamol, 1200 micrograms, was given with mouth rinsing and lung bioavailability was assessed by measuring plasma salbutamol levels and urine excretion of salbutamol. RESULTS: No differences were seen between innovator and generic salbutamol metered dose inhalers in plasma salbutamol levels, urinary salbutamol excretion, or extrapulmonary beta 2 activity. The maximum plasma salbutamol concentration (mean Cmax) and time to maximum concentration (median Tmax) were: Ventolin (2.93 ng/ml, 10 minutes), Salbulin (3.01 ng/ml, 10 minutes), Salamol (3.33 ng/ml, 10 minutes). The geometric mean ratio and 95% confidence interval for Cmax were: Salbulin/Ventolin 1.02 (0.69 to 1.41) and Salamol/Ventolin 1.13 (0.94 to 1.35). CONCLUSIONS: No differences are apparent between the two generic and innovator formulations of salbutamol metered dose inhaler in terms of lung bioavailability.